Handbook of environmental law - "Sahasranaman, P. B." (New Delhi, 2009)
Sahasranaman examines key issues related to environmental protection including sustainable development, environmental impact assessment, water resource management, waste management, forest conservation, wildlife protection, climate change, disaster management and rehabilitation, the intergenerational equity principle, and environmental taxes. Taking the impact of the 1972 UN Conference on the Human Environment as the starting point, he explains the provisions of various international conventions, constitutional amendments, and legislation enacted in India to tackle the gravest problems. He keeps the international context foregrounded throughout and provides valuable comparative analysis.
Keywords: Environmental law